(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: HCWs are at risk of coronavirus disease (COVID-19) because of prolonged and repeated exposure to patients and because HCWs work in a team and physical distancing is usually not possible among them. Therefore, this study aimed to identify the current status of knowledge, attitude and practice among HCWs in Peoples Dental College and Hospital, Kathmandu, Nepal. MATERIALS AND METHODS: This was a cross-sectional study conducted at People’s Dental College and Hospital, Kathmandu, Nepal through an online survey questionnaire from 1st July 2020 to 30th August 2020. A total of 163 HCWs were identified as eligible for study and 90 participants (HCWs) participated in the study. The data were collected through a structured questionnaire regarding COVID-19 and distributed via email, Facebook, Whatsapp. The responses were presented as numbers and percentages. RESULTS: Among 90 participants, majority were dentist 66(73.3%), 15(16.7%) were medical doctors and few 6(6.7%) were paramedical. Majority of the participants had proper knowledge of its transmission, incubation period, isolation and treatment and showed a positive practices towards preventive measures. A vast majority of health care workers were practicing precautionary measures such as washing hand 81(90%), wearing face mask while leaving home 87(96.7%), maintaining social distancing and healthy lifestyle 60(66.7%). However, fear of human to human transmission and transmission of infection to family member had a significant impact on attitude of some of the HCWs. CONCLUSIONS: The majority of HCWs had proper knowledge and practices toward COVID-19. However, the level of some knowledge and practices lower than that expected and negative attitude need to be addressed. Hence additional educational interventions are required for health care workers.